Operations management : concepts in manufacturing and services - Markland, Robert E.; Vickery, Shawnee K.; Davis, Robert A. (Cincinnati, OH : South-Western College, 1998)
Introduction. Manufacturing operations. Service operations. Operations strategy. Forecasting demand for products and services. Product planning and process design. Long-range capacity planning and facility location. Managing quality. Technological developments in operations management. Organization and human resources...
Keywords: Management; Production management